2005
DOI: 10.1128/iai.73.11.7768-7771.2005
|View full text |Cite
|
Sign up to set email alerts
|

Differential Use of the Two High-Oxygen-Affinity Terminal Oxidases of Brucella suis for In Vitro and Intramacrophagic Multiplication

Abstract: Expression of the high-oxygen-affinity cytochrome cbb3 and cytochrome bd ubiquinol oxidases of Brucella suis was studied in vitro and in the intramacrophagic niche, which was previously proposed to be oxygen limited. The cytochrome cbb3 oxidase was exclusively expressed in vitro, whereas the cytochrome bd oxidase was preferentially used inside macrophages and contributed to intracellular bacterial replication.Brucellosis, an anthropozoonosis encountered worldwide, is caused by the gram-negative intracellular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
65
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 21 publications
5
65
0
Order By: Relevance
“…The cbb3-type cytochrome c oxidase was specifically expressed in culture with maximal activation under microaerobiosis, whereas the cytochrome bd ubiquinol oxidase was preferentially expressed inside macrophages and involved in intracellular bacterial multiplication. These results indicated that Brucella needs a terminal oxidase with high affinity for oxygen for optimal survival inside the phagosomal compartment of the macrophage (18). In fact, the oxygen concentration inside phagosomes of stimulated macrophages is lower than that measured in the extracellular environment (11).…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…The cbb3-type cytochrome c oxidase was specifically expressed in culture with maximal activation under microaerobiosis, whereas the cytochrome bd ubiquinol oxidase was preferentially expressed inside macrophages and involved in intracellular bacterial multiplication. These results indicated that Brucella needs a terminal oxidase with high affinity for oxygen for optimal survival inside the phagosomal compartment of the macrophage (18). In fact, the oxygen concentration inside phagosomes of stimulated macrophages is lower than that measured in the extracellular environment (11).…”
mentioning
confidence: 55%
“…In a previous study, we showed that the two high-oxygen-affinity terminal oxidases of B. suis differently participated in adaptation to low-oxygen tension (18). The cbb3-type cytochrome c oxidase was specifically expressed in culture with maximal activation under microaerobiosis, whereas the cytochrome bd ubiquinol oxidase was preferentially expressed inside macrophages and involved in intracellular bacterial multiplication.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nitric oxide and reactive oxygen species are compounds released by macrophages to kill engulfed bacteria (20,21), and cytochrome bd oxidases have been shown to be less sensitive than other cytochrome oxidases to many such compounds (18,20). Consistent with cytochrome bd oxidase being important for bacterial survival within macrophages, cytochrome bd oxidase genes in Brucella suis, the cause of brucellosis, were shown to be induced upon macrophage engulfment, and were required for bacterial survival in the macrophage phagosomes (22). Together, these data suggest that cytochrome bd oxidases may play multiple roles in bacterial infection, helping bacteria survive periods of oxygen deprivation and exposure to cytotoxic agents released by the host immune system.…”
mentioning
confidence: 80%
“…The same oxygen-dependent switch is observed in R. sphaeroides: aa 3 -Cox is the predominant oxidase under aerobic conditions, while cbb 3 -Cox is mainly expressed at low oxygen concentrations or during the transition from anaerobic to aerobic growth (1,24). Also, many pathogenic bacteria, such as Brucella suis (22) or Campylobacter jejuni (54), use cbb 3 -Cox mainly at low oxygen concentrations. On the other hand, in Thiobacillus denitrificans cbb 3 -Cox is highly upregulated under aerobic conditions (2).…”
Section: Discussionmentioning
confidence: 99%